2017
DOI: 10.1590/1807-3107bor-2017.vol31.0049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deflection forces of orthodontic wires with different ligation types

Abstract: The aim of this study was to evaluate deflection forces of orthodontic wires of different alloys engaged into conventional brackets using several ligation types. Stainless steel, conventional superelastic nickel-titanium and thermally activated nickel-titanium archwires tied into conventional brackets by a ring-shaped elastomeric ligature (RSEL), a 8-shaped elastomeric ligature (8SEL) and a metal ligature (ML) were tested. A clinical simulation device was created especially for this study and forces were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
4
14
0
1
Order By: Relevance
“…In conventional brackets associated with copper nickel titanium archwires, the friction would be lower due to the smaller area of contact of the ligature with the archwire, and also due to the lower pressure exerted by the elastic ligature on the archwire. These findings corroborated those of studies in which lower pressure exerted by the elastic ligatures were found, making the pressure smoother and diminishing the points of contact of the wire with the internal part of the slot 21 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In conventional brackets associated with copper nickel titanium archwires, the friction would be lower due to the smaller area of contact of the ligature with the archwire, and also due to the lower pressure exerted by the elastic ligature on the archwire. These findings corroborated those of studies in which lower pressure exerted by the elastic ligatures were found, making the pressure smoother and diminishing the points of contact of the wire with the internal part of the slot 21 .…”
Section: Discussionsupporting
confidence: 88%
“…This fact may be explained by the more polished, smoother surface and greater rigidity of this wire, so that in spite of the pressure exerted by the clips of the active self-ligating brackets, the contact surface of this wire would not be increased. In the case of conventional brackets, the elastic ligature would not produce sufficient force to increase the surface of contact at the bracket/archwire interface, corroborating the findings of previous studies in which the composition of the archwire and clip of the bracket were reported 2,11,16,18,19,21 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…29 Although some studies reported no correlation between the amount of tooth crowding and pain perception, 4,5,18 this study showed that the increase of 1 mm of tooth crowding represents 1.1 times greater risk of pain. Tooth crowding may deflect the arch, increase the force 30,31 and consequently influence the pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…After the orthodontic archwire is put into the orthodontic bracket, the orthodontic force will be generated in the process of its shape restoration. 12 The orthodontic force will move the tooth to the target position, thus completing the space closure. 13,14 The magnitude of the orthodontic force is affected by not only the material characteristics of the archwire but also the shape parameters and the clearance distance.…”
Section: Introductionmentioning
confidence: 99%